PENTINGNYA SOSIAL MEDIAL DALAM MENINGKATKAN MINAT BELI DAN KEPUTUSAN PEMBELIAN DI ELYADA CAKE - Rivera Pantro Sukma; Ceren Evan Elyada (Komitmen: Jurnal Ilmiah Manajemen, 2022)
This study aimed to analyze the influence of social media Instagram and product quality on purchasing decisions through consumer buying interest at Elyada Cake Jakarta. This study uses primary data obtained from questionnaires with purposive sampling method with a sample of 200 respondents consisting of consumers who have purchased Elyada Cake products at least once. The data analysis method used in this research is validity test, reliability test, classical assumption test. While the hypothesis testing includes path analysis, MSI transformation, Sobel test, direct and indirect effect, path coefficient and coefficient of determination (R2). The author uses a quantitative descriptive method, namely by analyzing data using IBM SPSS Statistics 20. The results of the calculation of the coefficient of determination, social media Instagram and product quality on consumer buying interest, the coefficient of determination or R2 produced is 36.8%. Instagram social media, product quality and consumer buying interest in purchasing decisions obtained a coefficient of determination or R2 of 42.2%.